Enhancing filterability of activated sludge from landfill leachate treatment plant by applying electrical field ineffective on bacterial life - Akkaya, Gulizar Kurtoglu; Sekman, Elif; Top, Selin; Sagir, Ece; Bilgili, Mehmet Sinan; Guvenc, Senem Yazici (SPRINGER HEIDELBERG, 2017)
The aim of this study is to investigate filterability enhancement of activated sludge supplied form a full-scale leachate treatment plant by applying DC electric field while keeping the biological operational conditions in desirable range. The activated sludge samples were received from the nitrification tank in the leachate treatment plant of Istanbul's Odayeri Sanitary Landfill Site. Experimental sets were conducted as laboratory-scale batch studies and were duplicated for 1A, 2A, 3A, 4A, and 5A of electrical currents and 2, 5, 10, 15, and 30 min of exposure times under continuous aeration. Physicochemical parameters such as temperature, pH, and oxidation reduction potential in the mixture right after each experimental set and biochemical parameters such as chemical oxygen demand, total phosphorus, and ammonia nitrogen in supernatant were analyzed to define the sets that remain in the range of ideal biological operational conditions. Later on, sludge filterability properties such as capillary suction time, specific resistance to filtration, zeta potential, and particle size were measured for remaining harmless sets. Additionally, cost analyses were conducted in respect to energy and electrode consumptions. Application of 2A DC electric field and 15min exposure time was found to be the most favorable conditions to enhance filterability of the landfill leachate-activated sludge.
Keywords: Leachate; Activated sludge; Electric field; Electrocoagulation; Filterability; Aluminum electrode; WASTE-WATER; PERFORMANCE; ALUMINUM; REMOVAL; IRON; MBR; Environmental Sciences & Ecology